On the Genreal Composition of Komil Khorezmi Devon - Nuriddinov Shohobiddin Babayarovich (Researchparks Publishing, 2022)
In the article the genre structure of Kamil Khorezmi’s devon on the basis of primary sources is examined. It contains a detailed analysis of the poet’s poems, which do not include Devonian manuscripts and lithographs.